Terahertz Spectroscopy and Density Functional Theory for Non-Destructive Analysis of Anticoagulant Warfarin - Jiawei Li; Cong Zhang; Xiaohui Wang; Jinjing Zhang; Hanwen Liu; Xu Wu (Molecules)
Pharmaceutical quality control plays a critical role in safeguarding patient safety and ensuring therapeutic efficacy. However, conventional analytical methods are often hindered by laborious procedures and complex chemical preparation requirements. This study presents a rapid, non-destructive pharmaceutical analysis approach by introducing terahertz spectroscopy for the dual-parametric detection of the anticoagulant warfarin. Characteristic absorption peaks of warfarin within the 4–10 THz range were experimentally identified and theoretically resolved through density functional theory calculations, employing both single-molecule and unit cell models. Furthermore, three strong absorption peaks were selected to construct multivariate regression models correlating spectral parameters (peak intensity and area) with warfarin weight, achieving a detection limit of 0.641 mg within a 5 min analytical workflow. This approach enables simultaneous molecular fingerprint identification and quantitative determination without chemical modification, meeting the requirements for the rapid screening of active pharmaceutical ingredients.